Omega-3 status evaluation in australian female rugby league athletes: Ad libitum fish oil provision results in a varied omega-3 index - Anthony, R.; Jaffrey, N.; Byron, C.; Peoples, G. E.; Macartney, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Optimal omega-3 status, influenced by increased intake of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), is vital for physiological health. This study investigated the impact of ad libitum fish oil supplementation on the omega-3 status of female athletes in a professional rugby league team during a competitive season. Twenty-four (n = 24) athletes participated, and their omega-3 status was assessed using the Omega-3 Index (O3I) and arachidonic acid (AA) to EPA ratio through finger-prick blood samples taken at the start and end of the season. They were given access to a fish oil supplement (PILLAR Performance, Australia) with a recommended daily dose of four capsules per day (2,160 mg EPA and 1,440 mg docosahexaenoic acid). At the beginning of the season, the group mean O3I was 4.77% (95% confidence interval [CI: 4.50, 5.04]) and the AA to EPA ratio was 14.89 (95% CI [13.22, 16.55]). None of the athletes had an O3I exceeding 8%. By the season`s end, the O3I was a significantly increased to 7.28% (95% CI [6.64, 7.93], p < .0001) and AA to EPA ratio significantly decreased to a mean of 6.67 (95% CI [5.02, 8.31], p < .0001), driven primarily by the significant increase in EPA of +1.14% (95% CI [0.77, 1.51], p < .0001). However, these changes were varied between the athletes and most likely due to compliance. This study has demonstrated that using the objective O3I feedback scale is possible with elite female rugby athletes, but individual strategies will be required to achieve daily intake targets of EPA + DHA.